Consciência não-linear: de William James aos sistemas dinâmicos - Kinouchi, Renato Rodrigues (2004)
William James’s scientific psychology was developed in order to surpass precedent approaches such as both Rationalism and Associationism. His masterpiece, The Principles of Psychology (1890), has been a mark in the history of psychological science because James already took cognitive processes as relations between the organisms and their environments. In this doctoral work, three contemporaneous cognitive theories are interpreted through James’s ideas: Artificial Intelligence, Connectionism and Dynamical Systems. This analysis, however, neither concerns scientific psychology nor philosophy of mind — in precise terms, the former examines psychological facts, and the later categorizes mental phenomena. Notwithstanding, we have done a conceptualcomparative study that categorizes the explanations proposed by those three cognitive theories. To be sure, this work should be labelled as a Philosophy of Cognitive Science. It examines theories concerned with cognition; so it is a philosophical analysis on cognitive science